2019
DOI: 10.1016/j.anucene.2018.12.031
|View full text |Cite
|
Sign up to set email alerts
|

Coupled neutronic/thermal-hydraulic hot channel analysis of high power density civil marine SMR cores

Abstract: Core average power density of standard small modular reactors (SMR) are generally limited to 60-65 MW/m 3 , which is 40% lower than for a standard civil PWR in order to accommodate better thermal margins. While designing a SMR core for civil marine propulsion systems, it is required to increase its power density to make more attractive for future deployment. However, there are obvious thermal-hydraulic (TH) concerns regarding a high power density (HPD) core, which needs to be satisfied in order to ensure safe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…A higher enrichment was expected due to the lower UO 2 volume and the higher thermal neutron absorption of fertile 232 Th 11 . The use of duplex pellet designs also improves the ratio of neutron capture in fertile material to neutron absorption in fissile material which leads to an extended fuel burnup and core lifetime 11,57,58 . This has been demonstrated by previous work on duplex pellet utilization in PWR combined with axial pellet arrangement and checkboard rod configuration, which shows a 15% increase in burnup 14 .…”
Section: Thorium Seed‐and‐blanket Methodsmentioning
confidence: 78%
See 1 more Smart Citation
“…A higher enrichment was expected due to the lower UO 2 volume and the higher thermal neutron absorption of fertile 232 Th 11 . The use of duplex pellet designs also improves the ratio of neutron capture in fertile material to neutron absorption in fissile material which leads to an extended fuel burnup and core lifetime 11,57,58 . This has been demonstrated by previous work on duplex pellet utilization in PWR combined with axial pellet arrangement and checkboard rod configuration, which shows a 15% increase in burnup 14 .…”
Section: Thorium Seed‐and‐blanket Methodsmentioning
confidence: 78%
“…This indicates a higher breeding capacity, smaller core reactivity swing and longer core cycle 11 . The duplex is also used for the design of the SMR core with a high power density of 100 MW/m 3 58 …”
Section: Thorium Seed‐and‐blanket Methodsmentioning
confidence: 99%
“…• High power density SMR cores (Alam et al, 2019f) experience a core life penalty due to the associated reduction in fuel mass. Since this mixed coolant exhibits promise in offering longer core lifetime than the H 2 O coolant (Alam et al, 2019c), it has the potential to compensate this core life penalty.…”
Section: Discussionmentioning
confidence: 99%
“…The major challenge for the micro-heterogeneous duplex fuel arrangements is to meet the thermal-hydraulic margins since the most severe situation will be in the duplex pellet case where most of the power is generated in the UO 2 part of the fuel pellet. In order to confirm that all the thermal-hydraulic constraints are satisfied for the duplex fuel, 3D neutronic/thermal-hydraulic coupling of hybrid monte carlo MONK with sub-channel analysis COBRA-EN (Basile, 1999) code for hot channel analysis (Alam et al, 2019d) has been performed to evaluate key TH parameters such as: minimum departure from nucleate boiling ratio (MDNBR), heat flux, cladding, inner surface and fuel centreline temperatures, and pressure drop. Our study confirmed that thermal-hydraulic design requirements for the duplex fuel can be met and there will be no melting in the UO 2 region of the duplex pellet.…”
Section: Practical Considerations For the Duplex Fuelmentioning
confidence: 99%